Generous tax credits make tax filers more generous in their giving - Hickey, Ross; Payne, A. Abigail; Smith, Justin (My University, 2025)
The authors’ work provides depth for our understanding of how government policy affects the charitable sector. First, they demonstrate that the rationale for the tax credit is to increase giving. Second, they show that while charitable giving has remained relatively constant over the years, during the same period there has been decreasing rate of tax filers claiming the charitable donations tax credit. Third, they review the evidence of estimating donor responses to tax credits, showing that the tax credit is effective in stimulating generosity.
Keywords: Families, households and marital status; Government; Income, pensions, spending and wealth; Society and community